Okra (Abelmoschus esculentus) – a popular crop and vegetable - Tong, P.S. (UTAR Agriculture Science Journal, 2016)
Okra is a crop that is increasing in popularity. This is an account of how it is cultivated by a farmer in the Kinta Valley of Perak.